Measurement and Thermodynamic Modeling for CO2 Solubility in the N-(2-Hydroxyethyl) Piperazine + Water System - Li, Simeng; Kang, Gern Woo; Chen, Jian (Frontiers in Energy Research, 2021)
Amine scrubbing is the most important technique for capturing CO2. The cyclic diamine N-(2-Hydroxyethyl)-piperazine (HEPZ), a derivative of piperazine, with good mutual solubility in aqueous solution, a low melting point, and a high boiling point, has the potential to replace PZ as an activator added in the mixed amine system to capture CO2. In this study, the solubility of CO2 in aqueous HEPZ solutions was determined for three HEPZ concentrations and four temperatures. The VLE data for HEPZ-H2O were obtained using a gas–liquid double circulation kettle at pressure 30–100 kPa, and the thermodynamic model for the HEPZ-H2O-CO2 system was built in Aspen Plus based on the electrolytic non-random two-liquid (ENRTL) activity model. The physical parameters for HEPZ and the interaction parameters for ENRTL, along with reaction constants of carbamate reactions, were regressed. Using the thermodynamic model, the CO2 cyclic capacity, speciation with loading, and heat of reaction for the CO2 capture system by the aqueous HEPZ solution are predicted and analyzed.